Quantitative analysis of uncertainty in financial risk assessment of road transportation of wood in uruguay - Simões, Danilo [UNESP]; Mosquera, Gustavo Andrés Daniluk; Batistela, Gislaine Cristina [UNESP]; Passos, José Raimundo de Souza [UNESP]; Fenner, Paulo Torres [UNESP] (MDPI, 2016)
The uncertainty in road transportation of wood is inherent to its operational costs, to the amount of transported wood, to the traveled distance, to its revenue, and more. Although it is not possible to measure this uncertainty fully, it can be quantified by the investment risk, which is the probability and degree of financial loss. The objective of this study is to quantify the financial risk of the investment in wood transportation through Monte Carlo simulation, which uses realistic situations to estimate the operational cost of vehicles used for road transportation of wood. We quantify these uncertainties by assessing financial risk and building pseudorandom scenarios with the Monte Carlo simulation method, in addition to the Net Present Value techniques, the Modified Internal Rate of Return, and the Profitability Index, all commonly used in financial investment projects. The results show that the estimated operational costs are equivalent to the actual ones, along with the evidence that the cost of fuel, the driver’s manpower, and tires are components that mainly increase the degree of financial risk for an investment project in road transportation of wood. In contrast, optimizing the amount of transported wood and maximizing wood transportation cost have a significant and positive correlation with the volume of transported wood and the average price of wood transportation, leading to a reduction in the degree of financial risk.
Keywords: Cash flow; Economic viability; Eucalyptus species; Forest harvesting; Monte Carlo; Net Present Value; Transport costs; Truck; Wood mobilization